Engineering Geological and Geophysical Investigations to Characterise the Unstable Rock Slope of the Sopu Promontory (Gozo, Malta) - Davide Pistillo; Emanuele Colica; Sebastiano D’Amico; Daniela Farrugia; Federico Feliziani; Luciano Galone; Roberto Iannucci; Salvatore Martino (Geosciences, 2024)
Different engineering geological and geophysical investigations were performed at the Sopu promontory in the island of Gozo (Malta), involved in an impressive lateral spreading process due to the superimposition of a stiff limestone (ULC) on a ductile clay (BC). The applied techniques include: traditional geological and engineering geological surveys, unmanned aerial vehicles (UAV) survey, electrical resistivity tomography (ERT) survey, ground-penetrating radar (GPR) investigations, single-station seismic ambient noise measurements, and array seismic ambient noise measurements. The integration of the obtained results allowed us to reconstruct a subsoil model of the promontory that includes features related to the local geology of the slope and to the landslide process, as well as to define a conceptual model that describes the main evolution phases of the expansion process. The presence of back-tilted rock blocks with no features of polarization of Rayleigh waves evidenced the different failure mechanism of the rigid UCL plateau at the Sopu promontory with respect to the Selmun promontory, located in the close island of Malta, where the lateral spreading due to the same geological setting tends to produce unstable rock blocks with a toppling mechanism. This result encourages further future observations and analyses of this topic.